Stability Analysis of Yee Schemes to PML and UPML for Maxwell Equations (Journal of Computational Mathematics, 2021)
We utilize Fourier methods to analyze the stability of the Yee difference schemes forBérenger PML (perfectly matched layer) as well as the UPML (uniaxial perfectly matchedlayer) systems of two-dimensional Maxwell equations. Using a practical spectrum stabilityconcept, we find that the two schemes are spectrum stable under the same conditions formesh sizes. Besides, we prove that the UPML schemes with the same damping in bothdirections are stable. Numerical examples are given to confirm the stability analysis forthe PML method.